Incidence, Predictors, and Outcomes of Complete Angina Relief in Symptomatic Patients in the ISCHEMIA Trial - Ayesha Singh; Jack C. S. Rodman; David L. Brown (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Patients with chronic coronary disease experience less angina with revascularization plus optimal medical therapy compared with optimal medical therapy alone. However, patients may prefer to better understand their individual likelihood of complete angina relief associated with each treatment approach before selecting a strategy. We therefore sought to determine the incidence, predictors, and outcomes of complete angina relief in symptomatic patients treated with invasive management using revascularization plus optimal medical therapy or conservative therapy with optimal medical therapy alone in the ISCHEMIA (International Study of Comparative Health Effectiveness With Medical and Invasive Approaches) trial. Methods Angina was assessed using the Seattle Angina Questionnaire Angina Frequency (AF) score. We analyzed patients in the invasive management treatment arm with angina at baseline (Seattle Angina Questionnaire Angina Frequency <100) who underwent revascularization and all patients in the conservative therapy arm with angina at baseline. The primary outcome was angina status at 12 months defined as a Seattle Angina Questionnaire Angina Frequency=100 (complete angina relief) or Seattle Angina Questionnaire Angina Frequency <100 (persistent angina). The association of angina status with the composite of cardiovascular death/myocardial infarction was assessed at 5 years. Results Among 1376 patients in the conservative therapy arm with angina at baseline, 50% experienced complete angina relief at 12 months. Independent predictors included older age, male sex, recent angina onset, and less baseline angina. Among 1158 patients who underwent revascularization, 70% achieved complete angina relief. Predictors included younger age, nonsmoking, coronary artery bypass graft, and less baseline angina. Cardiovascular death/myocardial infarction rates at 5 years did not differ between patients with or without complete angina relief. Conclusions Complete angina relief at 12 months in symptomatic patients with chronic coronary disease was achieved in 70% of patients undergoing revascularization and 50% of patients treated ith conservative therapy and did not influence cardiovascular death/myocardial infarction outcomes. Registration https://ischemiatrial.org/; ISCHEMIA Trial. Accession Number HLB02742323a.